Review of the Gekko (Japonigekko) subpalmatus complex (Squamata, Sauria, Gekkonidae), with description of a new species from China - Lyu, Zhi-Tong; Lin, Chao-Yu; Ren, Jin-Long; Jiang, Ke; Zhang, Yin-Peng; Qi, Shuo; Wang, Jian (Zootaxa, 2021)
The gecko species Gekko (Japonigekko) subpalmatus was previously recorded with a relatively wide distribution from eastern, southern, and southeastern China. However, the populations in southern China are currently recognized as another valid species G. (J.) melli. In this study, we conduct a detailed morphological examination and phylogenetic analysis of the populations currently treated as G. (J.) subpalmatus or G. (J.) melli, which are collectively designated as the G. (J.) subpalmatus complex. Our results reveal that the G. (J.) subpalmatus complex comprises three evolutionarily independent taxa. The populations from Zhejiang, eastern China are G. (J.) subpalmatus, those from southern China are G. (J.) melli, while those from the Sichuan Basin, southwestern China represent a cryptic species, Gekko (Japonigekko) cib sp. nov.. Gekko (Japonigekko) cib sp. nov. can be distinguished from all congeners, by its divergence from other complex members in the CYTB and 16S genes, and a combination of morphological characteristics, especially in hemipenial morphology. Historic records of G. (J.) subpalmatus complex are also reviewed.